P112 The association between young age at first birth and mental health later in life: does the effect vary by birth cohort?. (13th September 2016) - Aitken, Z; Hewitt, B; Keogh, L; LaMontagne, AD; Bentley, R; Kavanagh, AM
Abstract : Background: It is well established that maternal age at childbirth has implications for women's mental health in the short term, however there has been little research regarding longer term implications and whether this association has changed over time. We investigated longer term mental health consequences for young mothers in Australia and contrasted the effects between three birth cohorts. Methods: Using thirteen waves of data from 4262 women aged 40 years or above participating in the Household, Income and Labour Dynamics in Australia Survey, we compared the mental health of women who had their first child aged 15 to 19 years, 20 to 24 years, and 25 years and older. Mental health was measured using the mental health component summary score of the SF-36. We used random-effects linear regression models to generate estimates of the association between age at first birth and mental health, adjusted for early life socioeconomic characteristics (country of birth, parents' employment status and occupation) and later life socioeconomic characteristics (education, employment, income, housing tenure, relationship status and social support). We examined whether the association changed over time, testing for effect modification across three successive birth cohorts. Results: In models adjusted for early life and later life socioeconomic characteristics, there was strong evidence of an association between teenage births and poor mental health, with mental health scores on average 2.76 to 3.96 points lower than for older mothers (Late Baby Boom: −3.96, 95% CI −5.38, −2.54; Early Baby Boom: −3.01, 95% CI −4.32, −1.69; Lucky Few: −2.76, 95% CI −4.34, −1.18), and evidence of an association for mothers aged 20 to 24 years compared to older mothers in the most recent birth cohort only (−1.09, 95% CI −2.01, −0.17). There was some indication (though weak) that the association increased in more recent cohorts. Conclusion: This study highlights that young mothers, and particularly teenage mothers, are a particularly vulnerable group to poor mental health outcomes compared to mothers aged 25 years and above, and there was some suggestion (though weak) that the health disparities increased over time.